Low-dose oral immunotherapy in immunoglobulin E-mediated food allergies - Ma, Dongxia; Zhu, Rongfei (Frontiers in Immunology, 2024)
Nowadays, the management of food allergies has increasingly moved from conventional oral immunotherapy (OIT) to low-dose OIT or low-dose OIT utilizing hypoallergenic foods. This shift is largely because the latter appears to induce oral tolerance with fewer adverse effects than the former. However, the mechanisms underpinning such differences remain unclear. To better understand these mechanisms, we conducted a comparative study scrutinizing the mechanisms of OIT, especially those of low-dose desensitization. We also summarized articles on low-dose OIT and low-dose OIT using hypoallergenic foods. We examined the efficacy, safety, and immunological parameters of low-dose OIT and those of low-dose OIT with hypoallergenic foods with the aim of shedding some light on low-dose OIT and its therapeutic application in inducing oral tolerance for individuals with food allergies.